2018
DOI: 10.1016/j.chembiol.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking Fucosylation: from Cell Adhesion to Immune System Regulation and Diseases

Abstract: Fucosylation is a biological process broadly observed in vertebrates, invertebrates, plants, bacteria, and fungi. Fucose moieties on cell-surface glycans are increasingly recognized as critical to many cell-cell interaction and signaling processes. One of the characteristic roles of fucose is its regulation of selectin-dependent leukocyte adhesion that has been well studied over the last two decades. Recent studies of fucose in immune cell development and function regulation have significantly expanded the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
161
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(172 citation statements)
references
References 113 publications
3
161
0
1
Order By: Relevance
“…Glycans are involved in a wide variety of physiologic and pathologic processes in eukaryotic cells after attachment to proteins or lipids through an enzymatic process called glycosylation 1 . In particular, fucosylated carbohydrates play an important role in the regulation of multiple cellular functions such as cell trafficking, immune cell development, and interaction with gut microbes and are generated through fucosylation mediated by fucosyltransferases (FUTs) [2][3][4] . Thus far, 13 FUT genes have been identified in human genome based on their acceptor specificities and protein sequences 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Glycans are involved in a wide variety of physiologic and pathologic processes in eukaryotic cells after attachment to proteins or lipids through an enzymatic process called glycosylation 1 . In particular, fucosylated carbohydrates play an important role in the regulation of multiple cellular functions such as cell trafficking, immune cell development, and interaction with gut microbes and are generated through fucosylation mediated by fucosyltransferases (FUTs) [2][3][4] . Thus far, 13 FUT genes have been identified in human genome based on their acceptor specificities and protein sequences 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the structural diversity of fucosylated glycans arises from thirteen fucosyl transferases that, in concert with other glycosyl transferases, create a wide variety of glycan epitopes. Fucosylated epitopes mediate many physiological and disease processes such as leukocyte adhesion during inflammation, fertilization, tissue development, and tumor metastasis . Therefore, the determination of exact fucoside positions and the affirmation of rearrangements are critical for the application of glycans as clinical biomarkers and to understand their biological roles at a molecular level.…”
Section: Figurementioning
confidence: 99%
“…In this review, the recent approaches for regulation of terminal fucose, poly-N-acetyllatosamine and sialic acid attachment on either N-glycans or O-glycans are discussed briefly. There are several comprehensive reviews for each category reported recently (71)(72)(73). The readers are recommended to these reviews for more detailed information and biomedical interests.…”
Section: B-6 Inhibition Of Specific Glycosyltransferases Of the Termmentioning
confidence: 99%
“…L-Fucose often exists as a terminal sugar in glycoconjugate glycans that are essential for either physiological or pathological activities, such as inflammation, bacterial and viral infections, tumor metastasis, and genetic disorders (72). Fucosyltransferases (FUTs) catalyze the incorporation of L-fucose residues, a process referred as fucosylation.…”
Section: B-6-1 Inhibition Of Fucosylationmentioning
confidence: 99%
See 1 more Smart Citation